PROSPEK PENGEMBANGAN ENERGI SURYA UNTUK KEBUTUHAN LISTRIK DI INDONESIA - Yandri, Valdi Rizki (Jurnal Ilmu Fisika, 2012)
Energy has important meaning in social and economics achievement to continously development and support to national economics activities. Energy consumption in Indonesia increases rapidly parallel with economics engagement and people growth. To supply energy requirement, renewable energy source should be developed. Renewable energy potency like solar energy hasn’t been used for big scale although Indonesia has big energy potency. Indonesia be included on tropical area which is exposed sun radiance almost year. It means solar energy has good prospects to be developed in Indonesia. Solar energy is one kind of energy which is gotten by converting sun calor energy to another type of energy. Solar energy can be used in form solar cell for electrical power plant. The utilization of solar cell can help people who lives on isolated area which is far from electrical network to use electrical energy.